Development of the nursing diagnosis risk for pressure ulcer - Cássia Teixeira dos Santos; Miriam de Abreu Almeida; Magáli Costa Oliveira; Marco Antônio de Goes Victor; Amália de Fátima Lucena
OBJECTIVE: The study objective was to develop the definition and compile the risk factors for a new Nursing Diagnosis entitled "Risk for pressure ulcer". The process was guided using the research question, "What are the risk factors for development of a PU and what is its definition?" METHOD: An integrative literature review was conducted of articles published in Portuguese, English or Spanish from 2002 to 2012 and indexed on the Lilacs/SCIELO, MEDLINE/PubMed Central and Web of Science databases. The final sample comprised 21 articles that provided answers to the research question. These articles were analyzed and summarized in charts. RESULTS: A definition was constructed and 19 risk factors were selected for the new nursing diagnosis, "Risk for pressure ulcer". CONCLUSIONS: Identification and definition of the components of the new nursing diagnosis should aid nurses to prevent pressure ulcer events.